Enhancement of Water Production Using Solar Still Coupled with High Power PV/AC Heater - Amri, Aufa (Universiti Teknologi PETRONAS, 2017)
Water purification technologies have expanded and grow widely over the years in order to cope with water limitation especially in countries experiencing water stress condition. Most of the technologies are costly and causing pollutions to the environment. Hence, more are looking forward for solar still as a method to produce safe and clean water for consumption without investing too much cost or causing harm to the environment. There are two types of solar still which are passive and active. This paper presents the performance of an active solar still coupled with high power PV/AC heater in producing distilled water. The experiment will be conducted in an open area filed in Universiti Teknologi PETRONAS (UTP) for 24 hours of period with weather forecast and solar radiation intensity obtained from Ipoh Meteorological Department. Other related parameters such as temperature of water, temperature of glass cover and ambient will be recorded during experiment conducted. To evaluate the efficiency of the experiment, another prototype of conventional solar still with the same dimensions and parameter will be conducted alongside with the active solar still. Water produced will then be tested in order to ensure safety of consumption that aligns with Malaysia National Drinking Water Quality Standards guidelines.